Mathematical Modeling in Natural Extract Anti-Reflection Coatings using Green Synthesis Method - Marathe, Snehal; Patil, B. P.; Waghmode, Shobha (Engineering, Technology & Applied Science Research, 2024)
The use of renewable energy sources to replace conventional energy sources like fossil fuels is essential. Solar panels are the most widespread technology for clear energy production. However, is crucial to raise the efficiency of solar panels. A large portion of sunlight is reflected by the front surface of the panel and thus the use of an Anti-Reflecting Coating (ARC) has become significant in raising the efficiency of solar panels, through reducing the reflection losses. The ARCs made of natural extracts were utilized to improve the efficiency of Silicon solar panels. The natural extracts were produced from Kailashpati fruit juice and Badminton ball tree flower powder. In the synthesis of these natural extracts, monometallic gallium chloride nanoparticles were used to check their effect on the efficiency of solar power generation. The novelty of this paper is the attempt to mathematically calculate the absorbance of the ARCs, at a particular wavelength, with the use of the refractive indices and thicknesses of ideal ARCs.